Common Operational Picture Technology in Law Enforcement: Three Case Studies, Baton Rouge, Louisiana, Camden County, New Jersey, Chicago, Illinois, 2015-2019 - Thorkildsen, Zoë ([Verlag nicht ermittelbar], 2022)
The use of common operational picture (COP) technology can give law enforcement and its public safety response partners the capacity to develop a shared situational awareness to support effective and timely decision-making. These technologies collate and display information relevant for situational awareness (e.g., the location and what is known about a crime incident, the location and operational status of an agency's patrol units, the duty status of officers). CNA conducted a mixed-methods study including a technical review of COP technologies and their capacities and a set of case studies intended to produce narratives of the COP technology adoption process as well as lessons learned and best practices regarding implementation and use of COP technologies. This study involved four phases over two years: (1) preparation and technology review, (2) qualitative case studies, (3) analysis, and (4) development and dissemination of results. This study produced a market review report describing the results from the technical review, including common technical characteristics and logistical requirements associated with COP technologies and a case study report of law enforcement agencies' adoption and use of COP technologies. This study provides guidance and lessons learned to agencies interested in implementing or revising their use of COP technology. Agencies will be able to identify how they can improve their information sharing and situational awareness capabilities using COP technology, and will be able to refer to the processes used by other, model agencies when undertaking the implementation of COP technology.